RESPONSIBILITY FOR SELF-DECEPTION - van Loon, Marie (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2018)
In this paper, I argue that Alfred Mele’s conception of self-deception is such that it always fulfils the reasons-responsiveness condition for doxastic responsibility. This is because self-deceptive mechanisms of belief formation are such that the kind of beliefs they bring about are the kind of beliefs that fulfil the criteria for doxastic responsibility from epistemic reasons responsiveness. I explain why in this paper. Mele describes the relation of the subject to the evidence as a biased relation. The subject does not simply believe on the basis of evidence, but on the basis of manipulated evidence. Mele puts forward four ways in which the subject does this. The subject could misinterpret positively or negatively, selectively focus, or gather evidence. Through these ways of manipulation, the evidence is framed such that the final product constitutes evidence on the basis of which the subject may believe a proposition that fits that subject’s desire that P. Whichever form of manipulation the subject uses, the evidence against P must be neutralized in one way or another. Successful neutralization of the evidence requires the ability to recognize what the evidence supports and the ability to react to it. These abilities consist precisely in the two parts of the reasons-responsiveness condition, reasons receptivity and reasons reactivity. In that sense, self-deceptive beliefs always fulfil the reasons-responsiveness condition for doxastic responsibility. However, given that reasons responsiveness is only a necessary condition for doxastic responsibility, this does not mean that self-deceived subjects are always responsible for their belief.